Toxicity and dosimetric analysis of nasopharyngeal carcinoma patients undergoing radiotherapy with IMRT or VMAT: A regional center's experience. (October 2020) - He, Ling; Xiao, Jianghong; Wei, Zhigong; He, Yan; Wang, Jingjing; Guan, Hui; Mu, Xiaoli; Peng, Xingchen
Highlights: VMAT may bring less late toxicities such as ototoxicity, trismus and temporal lobe injury. V45, V50 and Dmean to cochleae correlated significantly with ototoxicity. V65 and V70 to the TMJ correlated significantly with trismus. VMAT may provide more favorable dose distributions of targets and better sparing of normal tissue than IMRT. Abstract: Objectives: To observe the differences of dosimetric parameters and late toxicities in Nasopharyngeal Carcinoma (NPC) patients treated with intensity-modulated radiotherapy (IMRT) or volumetric modulated arc therapy (VMAT), which may provide the selective basis about radiation technology in clinical practices. Methods and materials: Dosimetric parameters and late toxicities were collected and retrospectively analyzed from 627 NPC patients (stage as I–IVA/IVB) between January 2010 and December 2015. Results: The median D2 of all targets and D50 of PGTVnd (regional lymph nodes) were lower in VAMT than those in IMRT, while the median D95 and D98 of PGTVnx (primary lesions) were higher in VMAT than those in IMRT ( p  < 0.05). Superior sparing of the organs at risk were observed in VMAT. The maximum dose of the brainstem, spinal cord, temporal lobes, temporomandibular joint, optic chiasm, and lens were lower in VMAT than those in IMRT, where the median dose reduction ranged from 0.56 to 3.56 Gy ( p  < 0.05). Meanwhile, the median parotid glands V30 in VMAT was reduced by approximately 2% compared to that in IMRT ( p  = 0.027). Regarding the late toxicities, ototoxicity, trismus, and temporal lobe injury were reduced by VMAT ( p  < 0.05). Furthermore, the late toxicities were correlative with the radiation dose of the corresponding OARs ( p  < 0.05). Conclusion: For NPC treatment plans, the VMAT might provide not only more favorable dose distributions of targets but also better sparing of normal tissue than observed in IMRT. Furthermore, VMAT possibly provides less treatment-related late toxicities such as ototoxicity, trismus, and temporal lobe injury.